2009
DOI: 10.1111/j.1365-2702.2008.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, social support, depressive symptoms and general health status of Taiwanese caregivers of persons with stroke or Alzheimer’s disease

Abstract: The findings of this study may be helpful for nurses and other health care professionals in designing effective interventions to minimise the negative impacts of stressors on the psychological and general health of caregivers in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 44 publications
0
49
0
4
Order By: Relevance
“…The greater the autonomy loss of older adults, the greater is the demand for care, which consequently overloads caregivers who provide care routinely. Similarly, studies addressing demented older adults revealed that behavior disorders caused by the disease are one of the leading causes of burden (4,14,23,24) . One of the purposes of care provided to demented patients is mainly related to keeping them physically safe, and reducing their anxiety and agitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater the autonomy loss of older adults, the greater is the demand for care, which consequently overloads caregivers who provide care routinely. Similarly, studies addressing demented older adults revealed that behavior disorders caused by the disease are one of the leading causes of burden (4,14,23,24) . One of the purposes of care provided to demented patients is mainly related to keeping them physically safe, and reducing their anxiety and agitation.…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of such a goal, however, is threatened when elderly individuals face health problems that cause loss of autonomy and independence. Among the most devastating problems is cognitive impairment (4) . Cognitive impairment among older adults consists of generalized and mild mental slowness and loss of precision, which progresses with age, when compared to younger individuals (5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staying in place in the community is however, deeply reliant on the unpaid labour of care partners (Pickard, 2010;Vreugdanhil, 2014). The lack of welfare support for care partners, coupled with the strain of being a full-time care partner, frequently results in poor health outcomes in care partners of a person with dementia (Huang et al, 2009;Brodaty et al, 2014).The implication for policy and practice is more needs to be done to support the welfare of people living in the community with dementia and the intermediate care services, providing care to those with dementia, living in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Despite guidelines on best practice being freely available, poor care practice is still a commonly reported occurrence in care homes (Care Quality Commission, 2014). Care in the community is largely provided by unpaid care partners (Hollander et al, 2009) and care partners of people with dementia have reported a decline in their physical health, a feeling of social isolation, depression and an increase in stress levels (Huang et al, 2009;Brodaty et al, 2014). Respite and educational interventions do not significantly reduce the impact that caring for a person with dementia in community settings has on mental and physical well-being (Pinquart and Sorensen, 2006;Jensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%